Selumetinib in Adult Neurofibromatosis 1 with Plexiform Neurofibroma - Carlen A. Yuen; Eleanor Chu; Ryan O’Connell; Bryan K. Sun; Raj Vyas; Michelle Zheng; Emma Elliott; Changrui Xiao (Pharmaceuticals, 2025)
Background/Objectives: Neurofibromatosis Type 1 (NF1) plexiform neurofibroma (PN) can cause morbidity, including disfigurement that can negatively impact social functioning. Historically, the mainstay treatment is surgical resection. However, complete resection is often prohibitive due to multiple nerve involvement. Moreover, post-operative recurrence is common. MEK inhibitors, including selumetinib and mirdametinib, have recently changed the treatment paradigm for these tumors. In 2020, selumetinib was FDA-approved for pediatric NF1 patients with inoperable symptomatic PNs, but selumetinib remains under investigation for their adult counterparts. In 2025, mirdametinib was FDA-approved for use in adults with symptomatic incompletely resectable NF1 PNs. Lower partial response rates have been reported with mirdametinib compared to selumetinib, but direct comparative analyses have not been conducted to establish the superiority of one agent over the other. Results: We present a case of a 38-year-old male with a right facial PN successfully treated with selumetinib, resulting in a 16.77% tumor volumetric reduction over 7 months. Selumetinib was well tolerated in our patient, with an asymptomatic Grade 3 CPK elevation that subsequently improved with a dose reduction. Conclusion: Our case adds to the growing body of evidence suggesting that selumetinib is effective and well tolerated in adult patients with NF1-associated PNs.